Environmental Problems of International Legal Regulation of Transboundary Pollution - BEKEZHANOV, Dauren; KOPBASSAROVA, Gulnurа; ZHUNISPAYEVA, Ainur; URAZYMBETOV, Talgat; SEILKASSYMOVA, Roza (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.v12.2(50).08, 2021)
This article is a comprehensive study on problems of legal protection of the environment from transboundary environmental pollution in the Republic of Kazakhstan. The study of international and national legislation in the field of environmental protection from transboundary environmental pollution was carried out, ways to solve legal problems related to transboundary environmental pollution were studied and proposed, theoretical concepts and practical recommendations were developed to increase the effectiveness of current legislation and the activities of state bodies in the field of environmental protection environment from transboundary environmental pollution. The theoretical significance of the study is that it will contribute to the further scientific development of conceptual problems of environmental cooperation in the field of preventing and preventing the negative effects of transboundary environmental pollution. The research itself, as well as the results obtained, will contribute to the further development of the domestic environmental law science.